Theory of Planned Behavior Constructs in Predicting Iron Supplement Consumption Adherence among Female Adolescents in Kudus, Central Java, Indonesia - Pelangi Pagi Kalimasadha; Revi Gama Hatta Novika; Ika Sumiyarsi Sukamto; Okid Parama Astiri; Arsita Eka Prasetyawati (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Anemia among female adolescents remains a significant public health problem in Indonesia. One of the main strategies to prevent anemia is the routine provision of iron supplementation tablets (TTD) for female adolescents. However, compliance to iron tablet consumption remains suboptimal. This study aimed to analyze the influence of the constructs of the Theory of Planned Behavior, on adherence to iron tablet consumption among female adolescents. Subjects and Method: This study employed a quantitative research design with a cross-sectional approach. The study was conducted among 275 female adolescents attending senior high schools at Ngembal Kulon and Jekulo sub districts, Kudus, Central Java, Indonesia. Participants were selected using proportional sampling. Data were collected using structured questionnaires and analyzed using logistic regression to determine the influence of attitude, subjective norms, perceived behavioral control, and intention on adherence to iron tablet consumption. Results: The results showed that attitude (OR=0.78; 95% CI=0.45–1.37; p=0.397) and intention (OR=0.82; 95% CI=0.44–1.51; p=0.520) was not significantly associated with compliance to iron tablet consumption. In contrast, subjective norms (OR=1.80; 95% CI=1.03–3.15; p=0.040) and perceived behavioral control (OR=4.67; 95% CI=2.40–9.10; p<0.001) were significantly associated with adherence to iron tablet consumption. Among these variables, perceived behavioral control was identified as the strongest determinant.in non-smoking behavior than male respondents (AOR = 2.52; 95% CI = 1.22 to 5.21; p = 0.012). Conclusion: Subjective norms and perceived behavioral control significantly influence adherence to iron tablet consumption among female adolescents.